STRATEGI WANITA RAWAN SOSIAL EKONOMI (WRSE) SEBAGAI UPAYA PEMENUHAN KEBUTUHAN HIDUP (Studi di Kelurahan Punggaloba, Kecamatan Kendari Barat, Kota Kendari) - Dewiyanti, Dewiyanti; Bahtiar, Bahtiar; Yusuf, Bakri (WELL-BEING: Journal of Social Welfare, 2021)
This study aims to determine the strategies undertaken by women who are prone to socio-economics (WRSE) in Punggaloba Village and to determine the inhibiting factors for women who are prone to socio-economics (WRSE) in an effort to meet the needs of life in Pungggaloba Village. This type of research is a qualitative descriptive study. The data collection technique was done by means of observation, interview and documentation with 7 WRSE informants in Punggaloba Village. The results of the research on the strategies carried out by WRSE in Punggaloba Village utilized their own WRSE skills and established small businesses to support all the needs in the family or the WRSE itself. And the inhibiting factor for WRSE is the lack of knowledge or education possessed by a WRSE because some of them have only graduated from junior high school, and most of them do not get assistance from the government which makes WRSE in Punggaloba Village, they have to struggle to meet their daily needs.